2017
DOI: 10.1007/s40279-017-0749-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation on Serum 25-Hydroxyvitamin D Concentrations and Physical Performance in Athletes: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Despite achieving sufficiency in vitamin D concentrations from ≥3000 IU supplementation, physical performance did not significantly improve. Between-study heterogeneity was large, and well-designed RCTs examining the effect of vitamin D supplementation on serum 25(OH)D concentrations, physical performance, and injuries in different sports, latitudes, ethnicities, and vitamin D status are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 54 publications
2
63
0
7
Order By: Relevance
“…Heaney and Holick 29 suggested that serum 25(OH)D levels need to be between 120-225 nmol.L -1 , though a recent meta-analysis suggested physical performance is not significantly improved. 30 The current study reported increases in serum 25(OH)D via vitamin D supplementation, the intervention group also demonstrated a limited increase in muscle strength and reduction in injury incidence. The data were from one vocational dance school in the UK and therefore further research needs to carried out in schools at different latitudes and diets, though research on Australian dance students found similar results 31 .…”
Section: Discussionmentioning
confidence: 50%
“…Heaney and Holick 29 suggested that serum 25(OH)D levels need to be between 120-225 nmol.L -1 , though a recent meta-analysis suggested physical performance is not significantly improved. 30 The current study reported increases in serum 25(OH)D via vitamin D supplementation, the intervention group also demonstrated a limited increase in muscle strength and reduction in injury incidence. The data were from one vocational dance school in the UK and therefore further research needs to carried out in schools at different latitudes and diets, though research on Australian dance students found similar results 31 .…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, some experts claimed that a daily intake of 10,000 IU would take months, or years to display symptoms of toxicity (46). Additionally, Farrokhyar et al (47), in a current review study, indicated that for athletes with low baseline values of 25(OH)D, supplementation between 3,000 and 5,000 IU seem to be sufficient for significantly increasing its level during winter months. Therefore, the daily vitamin D dose of 5,000 IU seems to be considered as acceptable for short-duration supplementation.…”
Section: Discussionmentioning
confidence: 74%
“…There are currently no guidelines in place for vitamin D supplementation in either professional or recreational athletes. However, the International Olympic Committee (IOC) and researchers within the area of vitamin D and sport (Larson‐Meyer ; Todd et al ; Farrokhyar et al ; Owens et al ) are in agreement that the regular monitoring of vitamin D status is imperative for the health and wellbeing of athletes. In addition, the IOC suggests that vitamin D should be supplemented (according to the US general population guidelines; 15–20 μg/day) dependent upon the athlete's skin type and level of UVB exposure (Maughan et al ), although there is no supplementation protocol provided for athletes.…”
Section: Vitamin D Supplementation Within Professional Athletesmentioning
confidence: 99%